Ewolucja modeli organizacyjnych w korporacjach transnarodowych a korporacje transnarodowe przyszłości - Urbanek, Joanna (Evolution of Organizational Models in International Corporations versus International Corporations of the Future, 2005)
The changes taking place within the structures and the strategies of international corporations are the main subjects raised in the article. Basing on the existing organisational models and having observed the contemporary companies the author of the paper identifies the incentives of transformation within international organisations. Tendencies in the contemporary world economy like vanishing of organisational boundaries and increasing flexibility requirement are especially highlighted. The stress has been put on understanding and modifying an international model, as the most sophisticated one.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1066, s. 385-394